Factors and effects of the increase in sicariato in Santo Domingo canton: a socio-legal and political analysis - Calva Vega, Yolanda Guissell; Zapata Valencia, Deivid Anderson; Cañizares Galarza, Fredy Pablo; Montece Giler, Salomón Alejandro (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
In Santo Domingo, Ecuador, the alarming increase in sicariato crimes during 2022-2023 has been documented by local judges and prosecutors. This research aimed to analyze the factors and effects of the sicariato rise in Santo Domingo Canton from a socio-legal and political perspective. The goal was to develop effective policies integrating punitive and preventive measures to address underlying socio-economic and cultural factors. Surveys and interviews with judges and prosecutors from the region were used as information gathering methods. Key findings highlight socio-economic inequality, the presence of criminal organizations, and institutional weakness as contributing factors to the issue. Both judges and prosecutors agree on the inadequacy of current criminal policies to effectively mitigate sicariato, emphasizing the urgent need for legal reforms and a comprehensive strategy that includes institutional strengthening and preventive programs.